1977
DOI: 10.1136/hrt.39.8.839
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve closure index. Echocardiographic index of severity of mitral stenosis.

Abstract: A new echocardiographic index of mitral valve diastolic closure, based on the rate of diastolic apposition of the anterior and posterior mitral leaflet echoes, was measured in 40 patients with mitral stenosis. This mitral valve closure index correlated highly significantly with the mitral valve orifice area (calculated from the Gorlin formula) (r= 0.87). Correlation between the diastolic closure rate (based on the EF slope) and the calculated valve area was poor (r=0.37).It is proposed that the mitral valve cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Several investigators (Segal et al, 1966;Edler, 1967;Effert, 1967;Gustafson, 1967) have claimed that the diastolic EF slope of the anterior mitral leaflet reflects the severity of mitral stenosis. As has previously been reported by others (Mary et al, 1973;Cope et al, 1975;Shiu, 1977), we also have frequently noticed discrepancies in patients with mitral stenosis between echocardiographic data and data obtained invasively by cardiac catheterisation and angiography. We have found that the EF slope is not a sensitive measure of the severity of mitral stenosis and is often misleading in individual patients.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Several investigators (Segal et al, 1966;Edler, 1967;Effert, 1967;Gustafson, 1967) have claimed that the diastolic EF slope of the anterior mitral leaflet reflects the severity of mitral stenosis. As has previously been reported by others (Mary et al, 1973;Cope et al, 1975;Shiu, 1977), we also have frequently noticed discrepancies in patients with mitral stenosis between echocardiographic data and data obtained invasively by cardiac catheterisation and angiography. We have found that the EF slope is not a sensitive measure of the severity of mitral stenosis and is often misleading in individual patients.…”
supporting
confidence: 76%
“…The rate of diastolic descent of the cage and ball is much reduced in the absence of significant obstruction across the prosthesis. If the movement of the anterior mitral leaflet in mitral stenosis is indeed related to movement of the valve ring, it is not surprising that the EF slope has little relation to the mitral valve area (Mary et al, 1973;Cope et al, 1975;Shiu, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier echocardiographic measures of MS severity include slope of the posterior left ventricular wall motion in diastole, 9 left atrial emptying index, 10 ejection fraction slope of the mitral valve motion, 11,12 and rate of diastolic closure of the mitral valve. 13 The advent of 2D and Doppler echocardiography allowed more accurate echocardiographic assessment of MS severity and echocardiography is currently the gold standard method for assessing MS severity. Among the currently used methods, planimetry of the mitral valve is probably the most accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of motion reduces deeper in the left ventricle, leaflet thickness may vary in different parts of the valve and the posterior leaflet may move in the normal direction in patients with proved mitral stenosis and hence all these features can be misleading. The E-F slope has been widely used to assess the severity of mitral valve obstruction but the method is insensitive and attempts have been made to improve sensitivity (Shiu, 1977). Furthermore, other conditions which can mimic mitral stenosis by producing a slow E-F slope include pulmonary arterial hypertension, left atrial myxoma, severe aortic stenosis and nonobstructive cardiomyopathy (McLaurin et al, 1973).…”
Section: Discussionmentioning
confidence: 99%